IMPLEMENTATION OF CARVING TRAINING TO PROMOTE SELF-RELIANCE AMONG P3 COMMUNITIES (BUSKERS, BEGGARS, AND SCAVENGERS) AT SANGGAR PENSI, BONDOWOSO REGENCY. - patmawati, dia; Imsiyah, Niswatul; Purnamawati, Frimha (Journal Of Educational Experts (JEE), 2025)
The aim of the research is to describe the implementation of sculpting training in the independence of the P3 community (buskers, beggars, scavengers) at Sanggar Pensi, Bondowoso Regency. The type of research used is descriptive with a qualitative approach. Determining the research location, researchers used the purposive area technique. Purposive sampling technique for determining informants. Data collection techniques through observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that in the implementation of sculpting training there are media, materials and learning methods that have a positive impact on emotional independence as shown by participants not getting angry easily when facing difficult situations, and not being irritable. Economic independence of training participants, especially for those who previously lived on the streets with uncertain income, but after taking part in carving training can meet their needs for clothing, food and can save money. Intellectual independence with changes in thought patterns and behavior in a more positive direction. Social independence is seen from the ability to interact with friends, other people and the surrounding community.